Medically assisted death’s legislation in European legal systems, in the perspective of a possible new Italian regulation (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay focuses on the different legislative rules which allow seriously ill patients to legally receive euthanasia or assisted suicide in Europe to examine the Italian legislation currently being approved on the same matter from a comparative legal perspective. The research about such an ethical theme involving several fundamental principles, like human dignity, life and solidarity, analyses the approaches of the Belgian, Dutch, Luxembourg and Spanish legal systems. The study will shed light on the essentiality of some preventive safeguards to support patients’ autonomy in consenting or refusing an end-of-life treatment, in line with the Italian Constitutional Court suggestions.
Keywords: Euthanasia; Assisted suicide; Personal Autonomy; Comparative law; End-of-life decisions